272 Factors Influencing Medical Student Future Career Choice – Why Not Surgery?. (28th February 2022) - Madden, S.; Clements, J.M.; Martin, N.; Kirk, S.J.
Abstract: Introduction: Decisions made by medical students on future career choice have demonstrated consistency with resulting postgraduate career path. The aim of this qualitative study was to identify factors influencing career choice amongst medical students in Northern Ireland. Method: An anonymous voluntary non-monetised survey consisting of binominal, Likert and free text responses was distributed to all medical students registered at Queen's University Belfast (QUB). Data was collected over 6 weeks in April-May 2021. Primary outcomes were factors influencing future career choice and the secondary outcomes were the impact of finance and mentorship on ultimate career choice. Local ethical approval was obtained. Results: 202 responses were received (Response rate 15%). 67% (n = 135) were female. One third of respondents remained undecided about their future career choice. Respondents were least likely to choose a career in Surgery (33%). Factors positively influencing career choice were academic interest and flexibility in working hours. Negative predictors of career choice were lack of interest in the area, perceived workload, and duration of training schemes. 71% (n = 144) of respondents reported that a subspecialty mentor would positively influence their career choice and two-thirds of respondents reported that financial factors would not influence their career decision. Conclusions: Surgery was the least the popular specialty. Mentorship, integrating flexibility in training and enhancing academic interest may create greater traction for prospective trainees to surgery.